DIPLOMASI EKONOMI INDONESIA TERHADAP TIONGKOK UNTUK MENINGKATKAN EKSPOR KARET ALAM DALAM KERANGKA ASEAN-CHINA FREE TRADE AGREEMENT (ACFTA) PERIODE 2015-2019 - Rachmasari Nur Al-Husin (2021)
Natural rubber is one of Indonesia's agricultural commodities that contributes to the country's foreign exchange reserves and the welfare of public such as farmers. Indonesia's natural rubber has been exported to many countries one of them is China, since their automotive and shipping industries began to develop. Especially since the existence of ACFTA that make tariff from various commodities including natural rubber to be eliminated through preferential tariff. Before and after the implementation of ACFTA, Indonesia's natural rubber export to China continued to increase. However, in 2014 China issued a policy of import duty on natural rubber, causing Indonesia to experience obstacle in exporting this commodity. Even though with ACFTA, export should increased but new policy from China caused Indonesia to be hampered in exporting natural rubber, so that Indonesia need to do economic diplomacy. This study aims to explain and analyze Indonesia's economic diplomacy towards China to increase natural rubber export in the framework of ACFTA period 2015-2019. This research used theory and concept international trade, free trade, and economic diplomacy theory in the form of commercial and trade diplomacy. Theory and concepts will be used to assist author in explaining and analyzing the research question. The research method in this research is qualitative, with a study case approach. This type of research is descriptive because author want to explain the result narratively through words. This research found that the form of commercial diplomacy that Indonesia undertook to increase natural rubber export to China are business forum, one on one business matching, and Indonesia's participation in CAEXPO. Meanwhile the form of trade diplomacy are AEM-MOFCOM and bilateral meeting between Indonesia and China.